Temporal trends and cohort variations of gender-specific major depressive disorders incidence in China: analysis based on the age-period-cohort-interaction model - Chao Guo; Xiyuan Hu (General Psychiatry)
Background Major depressive disorders (MDDs) impose substantial burdens on individuals and society; however, further detailed analysis is still needed for its long-term trends.Aims This study aimed to analyse the gender-specific temporal trends and cohort variations of MDD incidence among Chinese residents over the past three decades.Methods Employing the age-period-cohort-interaction model and leveraging data from the Global Burden of Disease Study 2019, this research identified and analysed incidence trends of MDD among Chinese males and females aged 5–94 years from 1990 to 2019 across three dimensions, encompassing age, period and birth cohort.Results The analysis reveals age-related effects, indicating heightened MDD risk among adolescents and older adults. Specifically, individuals entering the older adulthood at the age of 65–69 significantly increased the risk of MDD by 64.9%. People aged 90–94 years witnessed a 105.4% increase in MDD risk for the overall population, with females and males in this age group experiencing a 75.1% and 103.4% increase, respectively. In terms of period effects, the risk of MDD displayed a decline from 1990 to 1994, followed by a rebound in 2008. Cohort effects demonstrated diverse generational patterns, with generation I and generation III manifesting opposing ‘age-as-level’ trends. Generation II and generation IV exhibited ‘cumulative disadvantage’ and ‘cumulative advantage’ patterns, respectively. Age effects indicated an overall higher risk of MDD incidence in females, while cohort effects showed greater variations of MDD incidence among females.Conclusions The study underscores the substantial effects of age, period and cohort on MDD across genders in China. Priority interventions targeting vulnerable populations, including children, adolescents, older adults, females and the post-millennium birth cohort, are crucial to mitigate the impact of MDD.